2010
DOI: 10.5194/angeo-28-339-2010
|View full text |Cite
|
Sign up to set email alerts
|

On the time-scales of the downward propagation and of the tropospheric planetary wave response to the stratospheric circulation

Abstract: Abstract. Three datasets (the NCEP-NCAR reanalysis, the ERA-40 reanalysis and the LMDz-GCM), are used to analyze the relationships between large-scale dynamics of the stratosphere and the tropospheric planetary waves during the Northern Hemisphere (NH) winter. First, a crossspectral analysis clarifies the time scales at which downward propagation of stratospheric anomalies occurs in the lowfrequency band (that is at periods longer than 50 days). At these periods the strength of the polar vortex, measured by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Still, the presence of such a time lag alone is not sufficient to say that the signal originated in the stratosphere [ Plumb and Semeniuk , 2003]. Moreover, Nikulin and Lott [2010] recently found that the downward propagation of stratospheric anomalies occurs only at periods longer than 50 days. This suggests that the signals in response to the 11 year SC that we find formed within the troposphere itself.…”
Section: Discussionmentioning
confidence: 99%
“…Still, the presence of such a time lag alone is not sufficient to say that the signal originated in the stratosphere [ Plumb and Semeniuk , 2003]. Moreover, Nikulin and Lott [2010] recently found that the downward propagation of stratospheric anomalies occurs only at periods longer than 50 days. This suggests that the signals in response to the 11 year SC that we find formed within the troposphere itself.…”
Section: Discussionmentioning
confidence: 99%
“…This influence is related to radiative and chemical effects, but also to dynamical effects: some modes of stratospheric variability propagate downward, like the Quasi-Biennial Oscillation (QBO, Baldwin et al 2001) in the tropics, and the Arctic Oscillation (AO, Baldwin and Dunkerton 1999) in the mid latitudes. When the stratospheric anomalies reach the tropopause, they can potentially influence the surface climate, at least in the mid-latitudes (for the AO effect in the LMDZ mid-latitudes see for instance Lott et al 2005;Nikulin and Lott 2010). In order to take into account the impact of the stratospheric dynamics and chemistry in the coupled climate simulations, the LMDZ vertical grid was extended in the stratosphere, with a resolution close to a previous stratospheric version of LMDZ4 described by Lott et al (2005).…”
Section: Introductionmentioning
confidence: 99%